2015
DOI: 10.1063/1.4927428
|View full text |Cite
|
Sign up to set email alerts
|

A 1 kW-class multi-stage heat-driven thermoacoustic cryocooler system operating at liquefied natural gas temperature range

Abstract: This article introduces a multi-stage heat-driven thermoacoustic cryocooler capable of reaching cooling capacity about 1 kW at liquefied natural gas temperature range without any moving mechanical parts. The cooling system consists of an acoustically resonant double-acing traveling wave thermoacoustic heat engine and three identical pulse tube coolers. Unlike other traditional traveling wave thermoacoustic heat engines, the acoustically resonant double-acting thermoacoustic heat engine is a closed-loop configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…One potential application is natural gas liquefaction, which is accomplished by burning part of the gas [1]. At present, the highest reported efficiency of heat-driven regenerative natural gas liquefaction has been achieved by burning about 30% to liquefy the rest [2,3].…”
mentioning
confidence: 99%
“…One potential application is natural gas liquefaction, which is accomplished by burning part of the gas [1]. At present, the highest reported efficiency of heat-driven regenerative natural gas liquefaction has been achieved by burning about 30% to liquefy the rest [2,3].…”
mentioning
confidence: 99%
“…The key to achieving efficient energy conversion in a thermoacoustic system is to establish traveling-wave acoustic fields, i.e., the in-phase relationship between P1 and U1, across the regenerators [45]. Figure 9 shows the axial distribution of the phase difference between the pressure wave and volume flow rate in the thermoacoustic engine and heat pump.…”
Section: Axial Distribution Of Phase Fieldsmentioning
confidence: 99%
“…Developments in highefficient TADC natural gas liquefiers were accelerated by the development of the looped traveling-wave thermoacoustic engine (third generation). In 2015, a looped traveling-wave TADC operating at natural gas liquefaction temperatures was developed [26,27]. Experimental results showed that this system achieved a record exergy efficiency of 8 % and an overall cooling power of 1.2 kW at 130 K, which was capable of liquefying 65% of the natural gas while burning 35% natural gas.…”
Section: Introductionmentioning
confidence: 99%